MICROSCOPIC CHANGES IN THE LIVER CATS WITH CALICIVIRUS INFECTIONS - Борисевич, Б. В.; Лісова, В. В.; Бондаренко, О. В. (Scientific Progress & Innovations, 2013)
The results of histological studies of liver of cats that died from kalitsyvirusnoyi infection. Found distinct inflammatory changes characterized by expansion and overflow with blood blood vessels, inflammation of the parenchyma of organs and infiltration of inflammatory cells. These changes were accompanied by degeneration and necrosis of hepatocytes. In the liver capsule registered cell necrosis of hepatocytes, which did not have clear boundaries. Necrosis of liver cells characterized kariolisis.